Kyai's leadership model in Islamic educational institutions Pondok Pesantren: A literature study - Iwan Kurniawan; Eneng Muslihah; Encep Syarifudin; Supardi Supardi (IJGIE (International Journal of Graduate of Islamic Education), 2022)
This paper analyzes Kyai's leadership model applied to Islamic boarding schools. The method used is literature study. Related primary data were obtained from reference books and secondary data from several scientific articles from international and reputable national journals. Data analysis was carried out by collecting, analyzing, and drawing conclusions. The analysis results can be concluded that the Kyai leadership model applied to Islamic boarding schools consists of individual and collective leadership models. Some of the findings also found that there were spiritual leadership styles and charismatic leadership applied by Kyai in Islamic boarding schools. Further discussion is discussed on the subject matter of each topic.